Conflict-of-Laws Issues of Determining Administrative Jurisdiction and Deviation From Established Judicial Practice: The Case of Ukraine - Shcherbaniuk, Oksana; Bzova, Laura (Frontiers in Law, 2025)
The issue of the occurrence of the causes of conflicts of law is relevant, since its solution will depend on the clarity of the presentation of the legal problem. In addition, the formation of a proper functioning mechanism for resolving conflicts of law will increase the efficiency of legal regulation and ensure the stability and development of the legal system as a whole. It should be stated that the conflict problem before the twentieth century. was not the subject of special analysis and study. Everything, as a rule, was limited to stating the legal fact of the existence of collisions, as well as highlighting the most typical ways to overcome them. One of the obstacles to the proper functioning of the mechanism for determining and delimiting the administrative jurisdiction of cases of administrative offenses and other administrative cases is the existence of separate legal conflicts. At the same time, legal conflicts are characteristic not only in the issues of delimitation of jurisdiction for consideration of administrative and tort cases, but they also take place in the delimitation of the subjects of competence of administrative jurisdiction bodies. The imperfection of legislative technique and contradictions in laws, the presence of cases of regulation of the same legal relations by the norms of different laws leads to unequal application by the court of the same norms of substantive law and the adoption of different court decisions in similar legal relations. Therefore, the Constitution of Ukraine guarantees the right to appeal and cassation review of court decisions. As S. Shevchuk notes, acting according to the law, courts can violate the organic essence of law, taking the norm out of context. The norms of the law should be applied in the context of European standards – to promote the protection of human rights and freedoms in order to comply with the principle of the rule of law: finding a principle in which a norm can only be an element of argumentation.